The Influence of Local Wisdom-Based Leadership on Employee Professionalism - Imelda, Sonya; Khairul, Khairul; Pratomo, Hurip (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study aims to analyze the influence of local wisdom-based leadership on employee professionalism within the Personnel and Human Resource Development Agency of the Mentawai Islands Regency. Leadership rooted in local cultural values plays a significant role in shaping the behavior, work ethic, and professional performance of employees in regional government institutions. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation involving key informants, including agency leaders, staff, and community representatives. The findings reveal that leadership practices guided by local cultural wisdom—such as integrity, mutual respect, and collective responsibility—have a positive impact on enhancing employee professionalism. These values foster discipline, accountability, and a sense of belonging among civil servants, leading to improved work quality and public service delivery. Furthermore, the study highlights that leaders who internalize and apply local cultural values effectively bridge hierarchical gaps, strengthen organizational cohesion, and encourage ethical conduct aligned with community norms. However, challenges remain in maintaining consistency in applying these values amid generational and institutional changes. The study concludes that integrating local wisdom into leadership strategies is essential for building sustainable professionalism and organizational resilience in regional governance.